Provably secure biometric and PUF-based authentication for roaming service in global mobility network - E. Haodudin Nurkifli (Alexandria Engineering Journal)
The Global Mobility Network (GLOMONET) is crucial in the context of the Internet of Things (IoT) as it enables users to connect to the Internet from anywhere, anytime. However, while GLOMONET offers numerous benefits, it also present security challenges that need to be addressed. To ensure secure mutual authentication and prevent attacks such as impersonation, physical attacks, and DoS attacks, GLOMONET must provide strong anonymity, address loss of synchronization issues, and incorporate unclonable devices as an essential security feature. Therefore, this article proposes a new authentication protocol for GLOMONET that addresses these security issues. A formal analysis using Mao and Boyd's logic showed that the proposed protocol provides secure mutual authentication properties, and the RoR model demonstrated its resistance to attacks. In addition, the Programming Model Analysis (Scyther tool) confirmed that the proposed protocol meets security features and can withstand known attacks. The time complexity demonstration shows that the proposed protocol has a total complexity time of 5.482 seconds, the lowest time in the comparison subsection, indicating its suitability for use in GLOMONET.